Implementation Of The Meaning Of The Phrase “In Certain Circumstances And The Level Of Truth That Is Considered Sufficient According To The Head Of The Land Office” In Article 37 Paragraph (2) Of Government Regulation Number 24 Of 1997 On Land Registratio - Nuruddin, Nuruddin; Herlindah, Herlindah; Supriyadi, Supriyadi (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
This study aims to examine and analyze the implementation of the meaning of the phrase "in certain circumstances and the degree of truth that is considered sufficient according to the head of the Land Office" as written in Article 37 paragraph (2) of Government Regulation No. 24 of 1997 on Land Registration. The study was conducted on the island of Madura with the method of socio-legal research, which examines the perception and legal behavior of the community as well as their interaction with prevailing norms. Primary Data were obtained through interviews with the public and Land Office officials in four districts in Madura: Bangkalan, Sampang, Pamekasan, and Sumenep. Secondary Data were obtained from the study of documentation of legislation and Related Literature. The results showed that the implementation of the meaning of the phrase" in certain circumstances and the degree of truth that is considered sufficient according to the head of the Land Office " often led to different interpretations in the field. This has the potential to be abused by certain individuals who can damage the integrity of the land registration process. In addition, the lack of public understanding of land registration procedures led to many lands not being officially registered, creating legal problems in the future. This study suggests that the government clarify the criteria in the relevant regulations to avoid multi-interpretation and increase socialization to the public about the importance of land registration by legislation, in order to provide legal certainty and protect land rights.